2001
DOI: 10.1182/blood.v97.11.3596
|View full text |Cite
|
Sign up to set email alerts
|

CD99 expression is positively regulated by Sp1 and is negatively regulated by Epstein-Barr virus latent membrane protein 1 through nuclear factor-κB

Abstract: Epstein-Barr virus (EBV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
(46 reference statements)
1
9
0
1
Order By: Relevance
“…CD99 is expressed on most of human tissues and the significant role of CD99 in tumorigenesis was only documented in Hodgkin's disease, in which the loss of CD99 has been shown to play a critical role in the formation of Hodgkin's and Reed-Sternberg cells (29)(30)(31). The results from our study also suggest that the downregulation of CD99 type I could be associated with dedifferentiation of tumor cells in gastric adenocarcinomas.…”
Section: Discussionsupporting
confidence: 55%
“…CD99 is expressed on most of human tissues and the significant role of CD99 in tumorigenesis was only documented in Hodgkin's disease, in which the loss of CD99 has been shown to play a critical role in the formation of Hodgkin's and Reed-Sternberg cells (29)(30)(31). The results from our study also suggest that the downregulation of CD99 type I could be associated with dedifferentiation of tumor cells in gastric adenocarcinomas.…”
Section: Discussionsupporting
confidence: 55%
“…Sp1 binds to six sites located in the region between Ϫ122 and Ϫ60 relative to the transcription initiation site of the p21 gene (45). The potential involvement of Sp1 in the LMP1-mediated repression of the p21 promoter is supported by the recent finding showing that LMP1 repressed the transcription driven by the promoter of the CD99 gene, which encodes for a protein that is involved in cell adhesion, differentiation, and apoptosis in T cells and neurons (46). The proximal promoter of the CD99 gene contains an Sp1 site, and this site appears to be indispensable for the repressive activity of LMP1 (46).…”
Section: Lmp1 Is An Inhibitor Of the Basal And Tgf␤-inducible Activitmentioning
confidence: 93%
“…Recently, Grimm et al demonstrated that LMP1 inhibits Bax through a direct binding of p50/p65 heterodimer on the promoter (19). Alternatively, another NF-B-repressed target gene of LMP1, CD99, lacks a NF-B consensus sequence in its promoter, suggesting an indirect NF-B-mediated recruitment of corepressors or a squelching effect of coactivators (34). Lack of a NF-B binding element in the LMP1 promoter suggests that DNA binding of p65 is not required for the p65-mediated inhibition of pLMP1.…”
Section: Vol 80 2006 Lmp1 Autoactivation During Type II Latency 7389mentioning
confidence: 99%
“…This transactivation is further enhanced by two other latent proteins, EBNA-LP and EBNA3C (45,67). Alternatively, pLMP1 can be activated in an EBNA2-independent manner by several cellular proteins, including interferon regulatory factor 7 (IRF7) (42), STAT3 (7), Notch1 (22), Sp1 (34), USF, ATF1, and CREB1 (53). pLMP1 activity can also be inhibited by a Max-Mad1 and histone deacetylase (HDAC) complex (54).…”
mentioning
confidence: 99%